2009
DOI: 10.1097/mbp.0b013e3283330a67
|View full text |Cite
|
Sign up to set email alerts
|

Raising the arm before cuff inflation increases the loudness of Korotkoff sounds

Abstract: Korotkoff sounds can be enhanced by elevating the arm overhead for 30 s before inflating the cuff, and then bringing the arm to the usual position to continue in the blood pressure measurement. This manoeuvre leads to louder systolic Korotkoff sounds and does not have an effect on measured blood pressure levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Verrij et al [20] showed that raising the arm before beginning a standard brachial sphygmomanometry measurement significantly increased the amplitude of the Korotkoff sound. They suggested that the lower filling pressure of the arterial system distal to the cuff results in lower wall tensions than normal and in larger pressure differences in the vascular system proximally and distally of the cuff may result in louder Korotkoff sound.…”
Section: Discussionmentioning
confidence: 99%
“…Verrij et al [20] showed that raising the arm before beginning a standard brachial sphygmomanometry measurement significantly increased the amplitude of the Korotkoff sound. They suggested that the lower filling pressure of the arterial system distal to the cuff results in lower wall tensions than normal and in larger pressure differences in the vascular system proximally and distally of the cuff may result in louder Korotkoff sound.…”
Section: Discussionmentioning
confidence: 99%